Dynamic Effects of Educational Assortative Mating on Labor Supply - Rania Gihleb; Osnat Lifshitz (Institute for the Study of Labor (IZA), 2016)
In 30% of young American couples the wife is more educated than the husband. Those women are characterized by a substantially higher employment (all else equal), which in turn amplifies income inequality across couples. Using NLSY79, we formulate and structurally estimate a dynamic life-cycle model of endogenous marriage and labor supply decisions in a collective framework. We establish that the education gap at the time of marriage, produces dynamic effects due to human capital accumulation and implied wage growth. Inequality between couples is largely driven by the persistence in labor supply choices and only slightly affected by assortative matching.
Keywords: J22; J12; J24; J31; 330; educational assortative mating; female labor supply; human capital; inequality